Comparative study of different types of waterproofing screeds with a focus on radon permeability after the freeze-thaw exposure - Michal Nývlt; Jiří Pazderka; Martin Jiránek; David Hes (Acta Polytechnica CTU Proceedings)
This study aims to verify and independently compare the functionality of waterproofing screeds against the effect of radon with the influence of freezing cycles. The effect of freezing cycles on the sealing ability against radon was investigated on polymer, silicate (mineral), and bituminous screeds. The measured values correspond to commonly used insulation materials, confirming the correctness of the measurement and evaluation methodology. Waterproofing screeds are shown to be suitable materials for substructure applications. Unlike waterproofing made from strips such as bitumen membrane or PVC membrane, they do not contain joints and can thus offer a more reliable solution. The measured values show minimal differences between the tested waterproofing screeds after freeze-thaw exposure. Especially in the case of silicate (mineral) screed and polymer screed, the effect is negligible. The greatest effect of freeze-thaw cycles on the ability to seal against radon was observed for bitumen screeds.